EFFECT OF FERRO ELECTRIC THICKNESS ON NEGATIVE CAPACITANCE FET (NCFET) - Hashim, Muhaimin Bin Mohd; Alam, AHM Zahirul; Darmis, Naimah Binti (IIUM Engineering Journal, 2020)
Conventional Field Effect Transistor (FET) are well known to require at least 60mV/decade at 300K change in the channel potential to change the current by a factor of 10. Due to this, 60mV/decade becomes the bottleneck of this day transistor. A comprehensive study of the Negative Capacitance Field Effect Transistor (NCFETis presented. This paper shows the effect of ferroelectric material in MOSFET structure by replacing the insulator in the conventional MOSFET. It should be possible to obtain a steeper subthreshold swing (SS) compared to the one without a ferroelectric material layer, thus breaking the fundamental limit on the operating voltage of MOSFET. 27% of the subthreshold slope reduction is observed by introducing ferroelectric in the dielectric layer compared to the conventional MOSFETs. Hence, the power dissipation in MOSFET can be mitigated and shine to a new technology of a low voltage/low power transistor operation. ABSTRAK: Transistor Kesan Medan Konvensional (FET) terkenal memerlukan sekurang-kurangnya 60mV / dekad pada 300K perubahan pada saluran yang berpotensi untuk mengubah arus dengan faktor 10. Oleh kerana itu, 60mV / dekad menjadi hambatan transistor hari ini. Kajian komprehensif mengenai Negative Capacitance Field Effect Transistor (NCFETis dikemukakan. Makalah ini menunjukkan kesan bahan ferroelektrik dalam struktur MOSFET dengan mengganti penebat dalam MOSFET konvensional. Sebaiknya dapatkan swing swing subthreshold (SS) yang lebih curam berbanding dengan satu tanpa lapisan bahan ferroelektrik, sehingga melanggar had asas pada voltan operasi MOSFET. 27% pengurangan cerun subthreshold diperhatikan dengan memperkenalkan ferroelektrik di lapisan dielektrik berbanding dengan MOSFET konvensional. Oleh itu, pelesapan daya dalam MOSFET dapat dikurangkan dan bersinar dengan teknologi baru operasi transistor voltan rendah / kuasa rendah.